REPRESENTASI GENDER DALAM CERITA TEMATIK BILINGUAL AKU CINTA KEBERSIHAN KARYA RIAN F. RAHMAN - Sari, Bernadeta; Miranda, Dian; Linarsih, Andini (Universitas Tanjungpura, 2023)
Gender representation in children's story books, especially bilingual thematic storybooks to find out how gender is depicted in children's stories. This type of research uses the data analysis content of the Miles and Huberman models. The sample/subject in this study was a bilingual story book written by Rian F. Rahman. In the bilingual thematic story I Love Cleanlines (I Love Cleanlines), the researcher saw that in the children's story there are roles of men, namely fathers, boys and girls, namely mothers. Based on the results of the analysis of bilingual thematic storybooks